Preparation method of amorphous magnetic powder core with high magnetic conductivity and low loss

Through atomization powder making, particle size grading and inorganic-organic composite coating treatment, the problems of insufficient magnetic permeability, loss and DC bias performance of the existing amorphous magnetic powder core are solved, and higher permeability and lower loss are achieved, which is suitable for applications with higher power and frequency.

CN119724901APending Publication Date: 2025-03-28ANHUI ONE MAGNET ELECTRONIC CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411927018.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing amorphous magnetic powder cores have shortcomings in magnetic permeability, loss and DC bias performance, and are difficult to meet more stringent and complex application needs.

Method used

Amorphous magnetic powder cores are prepared by atomizing powder making, particle size grading and inorganic-organic composite coating treatment. The specific steps include atomizing treatment in the mixed inert gas, particle size grading, and coating the sulfuric acid-phosphoric acid-boric acid composite passivation solution and polyacrylic acid-polyethylene glycol mixture, and finally bonding with MnZn ferrite binder.

Benefits of technology

It significantly improves the permeability and DC bias performance of the amorphous magnetic powder core, while reducing losses, and can meet the application needs of higher power and frequency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724901A_ABST
    Figure CN119724901A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an amorphous magnetic powder core with high magnetic conductivity and low loss, and belongs to the technical field of preparation of amorphous magnetic powder cores. The preparation method comprises the following steps: S1, atomizing to prepare powder; s2, grain size grading; and S3, carrying out inorganic-organic composite coating treatment. In the atomization powder preparation process, mixed inert gas (nitrogen, argon and a small amount of oxygen) is used for atomization treatment; the particle size distribution ensures that the powder has proper apparent density; in the inorganic-organic composite coating treatment process, a sulfuric acid-phosphoric acid-boric acid composite passivation solution is firstly used for internal passivation treatment, then a polyacrylic acid-polyethylene glycol mixed solution is used for external insulation coating, and a MnZn ferrite binder and an acetone mixed solution are used for bonding. Compared with the prior art, the amorphous magnetic powder core prepared through the method has higher effective magnetic conductivity, lower loss and better direct current bias performance, and the application requirements of higher power and frequency are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of amorphous magnetic powder cores, and in particular relates to a method for preparing an amorphous magnetic powder core with high magnetic permeability and low loss. Background Art

[0002] With the rapid development of electronic information technology and new energy vehicles, the demand for magnetic materials is growing. Among them, amorphous magnetic powder core, as a new type of magnetic material, has attracted widespread attention due to its advantages such as high saturation magnetic induction intensity, low hysteresis loss and good temperature stability.

[0003] However, existing amorphous magnetic powder cores have certain limitations. First, the preparation process of amorphous magnetic powder cores is relatively complicated. It is necessary to use a high-speed rotation method to prepare amorphous strips, and then cut and anneal them to make magnetic powder cores. The preparation cycle is long and the production cost is high. Secondly, the existing amorphous magnetic powder cores still need to be improved in terms of high magnetic permeability and high DC bias to meet more stringent and complex application requirements.

[0004] A patent application with publication number CN116435085A discloses a method for preparing an iron-based amorphous magnetic powder core, which prepares a super-hydrophobic nano-SiO2 insulating layer through surface modification with a silane coupling agent and a sol-gel method to obtain a low-loss magnetic powder core with excellent performance at high frequencies. However, this method will reduce the density of the magnetic powder core and thus reduce the effective magnetic permeability.

[0005] A patent application with publication number CN114309628A discloses a method for preparing amorphous magnetic powder. By adopting hydrogen-based reduction and atomization technology, FeSiBPNbCr amorphous magnetic powder is prepared using low-cost raw materials such as high-phosphorus iron ore, which simplifies the process flow and can effectively improve the magnetic permeability of the amorphous magnetic powder. However, the preparation method of this patent will lead to increased losses, thereby affecting the performance of the product.

[0006] In view of the above problems, the present invention provides a method for preparing a high magnetic permeability and low loss amorphous magnetic powder core, aiming to simplify the preparation process, reduce production costs, and improve the magnetic permeability of the magnetic powder core to meet market demand. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a high permeability and low loss amorphous magnetic powder core, so as to solve the problems of low saturation magnetic induction intensity, high hysteresis loss and low DC bias of the magnetic powder core in the prior art.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A method for preparing a high magnetic permeability and low loss amorphous magnetic powder core comprises the following steps:

[0010] S1, atomization powder making;

[0011] S2, particle size gradation;

[0012] S3, inorganic-organic composite coating treatment;

[0013] In the atomization powder making process, a mixed inert gas is used for atomization treatment, and the mixed inert gas is nitrogen, argon and a small amount of oxygen; in the inorganic-organic composite coating process, a sulfuric acid-phosphoric acid-boric acid composite passivation solution is first used for internal passivation treatment, and then a polyacrylic acid-polyethylene glycol mixed solution is used for external insulation coating, and a MnZn ferrite binder and acetone mixed solution is used for bonding.

[0014] Furthermore, step S1 atomization powder making includes the following steps:

[0015] S11, smelting the raw materials to obtain an alloy solution;

[0016] S12, atomizing the alloy solution under a mixed inert gas atmosphere to obtain an alloy powder precursor;

[0017] S13, cooling the alloy powder precursor to obtain amorphous alloy powder.

[0018] Further, the raw material in step S11 is a FeCoSiB alloy. Preferably, the components of the raw material include, by mass percentage: Si: 2-8%, Co: 15-25%, B: 3-8%, Cr: 0.5-3%, Nd: 0.5-2%, Nb: 0.5-5%, Cu: 0.5-5%, Al: 0.5-5%, Ga: 0.5-5%, C: 0.1-2%, and the remainder is Fe and impurities that are difficult to remove;

[0019] The smelting temperature in step S11 is 1350° C.-1500° C., and the smelting time is 2-3 hours.

[0020] Furthermore, the mass ratio of nitrogen, argon and oxygen in the mixed inert gas in step S12 is 30%-40%: 60%-70%: 0.2%;

[0021] The atomization pressure of the atomization process in step S12 is 2.5-5 MPa, and the atomization time is 20-40 min.

[0022] Furthermore, the specific steps of the particle size distribution in step S2 are:

[0023] The amorphous alloy powder obtained in step S1 is subjected to particle size classification to obtain a finished amorphous alloy powder having a fineness modulus D10 of 3-5 μm, a median particle size D50 of 10-12 μm, and a D90 of 16-19 μm.

[0024] Furthermore, step S3 of inorganic-organic composite coating treatment includes the following steps:

[0025] S31, performing inner layer passivation treatment on the surface of the finished amorphous alloy powder obtained in step S2: heating the finished amorphous alloy powder obtained in step S2 to 103-110° C., adding sulfuric acid-phosphoric acid-boric acid composite passivation solution and stirring for 20-30 min, and drying at 105-120° C. for 0.5-1.5 h after the stirring, to obtain amorphous soft magnetic powder;

[0026] S32, performing outer insulation coating on the amorphous soft magnetic powder: adding polyacrylic acid-polyethylene glycol mixed solution to the amorphous soft magnetic powder and stirring for 20-30 minutes, taking out after the stirring, and drying at 110-130° C. for 1-2 hours to obtain the coated amorphous soft magnetic powder;

[0027] S33, mixing the MnZn ferrite binder and acetone mixed solution into the coated amorphous soft magnetic powder, stirring for 20-30 minutes, taking out after the stirring, and drying at 120-140° C. for 1-2 hours to obtain a finished amorphous magnetic powder;

[0028] S34, pressing the finished amorphous magnetic powder under a pressure of 1200-1600 MPa for 10-20 seconds to form an amorphous magnetic powder core with an outer diameter of 14 mm and an inner diameter of 8 mm.

[0029] Furthermore, in step S31, the mass ratio of sulfuric acid-phosphoric acid-boric acid composite passivation solution to the finished amorphous alloy powder is 2‰-14‰, and the mass ratio of sulfuric acid, phosphoric acid and boric acid in the sulfuric acid-phosphoric acid-boric acid composite passivation solution is 20%-30%: 40%-50%: 30%-40%.

[0030] Furthermore, in step S32, the mass ratio of the polyacrylic acid-polyethylene glycol mixed solution to the amorphous soft magnetic powder is 5‰-15‰, and the mass ratio of polyacrylic acid to polyethylene glycol in the polyacrylic acid-polyethylene glycol mixed solution is 40%-50%:50%-60%.

[0031] Furthermore, in step S33, the mass ratio of the MnZn ferrite adhesive to the amorphous soft magnetic powder after the coating process is 2-4%, and the mass ratio of the acetone solution to the amorphous soft magnetic powder after the coating process is 4-8%.

[0032] Further, the MnZn ferrite binder in step S33 is prepared by the following steps:

[0033] The iron salt, manganese salt and zinc salt are prepared into an iron-manganese-zinc solution in a mass ratio of 6:2:2, n-hexanol and sodium dodecylbenzene sulfonate are prepared into n-hexanol-sodium dodecylbenzene sulfonate in a mass ratio of 1:3, the iron-manganese-zinc solution and the n-hexanol-sodium dodecylbenzene sulfonate with a mass ratio of 5‰ of the iron-manganese-zinc solution are mixed, and then 1% ammonia water-ammonium persulfate with a mass ratio of ammonia water to ammonium persulfate of the iron-manganese-zinc solution is added to prepare manganese-zinc ferrite powder, wherein the mass ratio of ammonia water to ammonium persulfate in ammonia water-ammonium persulfate is 1:2, the manganese-zinc ferrite powder is mixed with polypropylene and KH570 in a mass ratio of 8:0.5:1.5 and ground for 2 hours to obtain a MnZn ferrite binder.

[0034] Beneficial effects of the present invention:

[0035] (1) The present invention provides a method for preparing a high-permeability and low-loss amorphous magnetic powder core, comprising three steps of atomization powder making, particle size grading and inorganic-organic composite coating treatment; the prepared amorphous magnetic powder core has higher magnetic permeability, lower loss and better DC bias performance, and can meet the application requirements of higher power and frequency.

[0036] (2) In the inorganic-organic composite coating process of the present invention, a sulfuric acid-phosphoric acid-boric acid composite passivation solution is first used for internal passivation treatment, and then a polyacrylic acid-polyethylene glycol mixed solution is used for external insulation coating, and a MnZn ferrite binder and acetone mixed solution are used for bonding; compared with a single phosphoric acid as a passivating agent, the inorganic-organic composite coating significantly improves the magnetic permeability of the amorphous magnetic powder core material, and the loss is also significantly improved.

[0037] (3) In the atomization powder making process of the present invention, a mixed inert gas (nitrogen, argon and a small amount of oxygen) is used for atomization treatment to obtain a rapidly cooled amorphous alloy powder; compared with a single nitrogen atmosphere, the tap density of the amorphous magnetic powder core is effectively improved, thereby improving the magnetic permeability of the material; at the same time, the small amount of oxygen injected forms a tight oxide layer on the surface of the amorphous alloy powder, thereby reducing the loss of the amorphous magnetic powder core.

[0038] (4) The present invention significantly improves the DC bias performance of the amorphous magnetic powder core material by adding rare alloy elements such as Ga, Nd, and Nb to the raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The present invention will be further described below in conjunction with the accompanying drawings.

[0040] Figure 1 is a scanning electron microscope image of the double-layer insulation coating of the amorphous magnetic powder core prepared in Example 1;

[0041] Figure 2 It is a schematic diagram of the effect of changes in magnetic induction intensity on the loss of different test cases. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Preparation Example 1

[0044] This preparation example provides a MnZn ferrite binder, and the specific preparation steps are as follows:

[0045] The iron salt, manganese salt and zinc salt are prepared into an iron-manganese-zinc solution in a mass ratio of 6:2:2, n-hexanol and sodium dodecylbenzene sulfonate are prepared into n-hexanol-sodium dodecylbenzene sulfonate in a mass ratio of 1:3, the iron-manganese-zinc solution and the n-hexanol-sodium dodecylbenzene sulfonate with a mass ratio of 5‰ of the iron-manganese-zinc solution are mixed, and then 1% ammonia water-ammonium persulfate with a mass ratio of ammonia water to ammonium persulfate of the iron-manganese-zinc solution is added to prepare manganese-zinc ferrite powder, wherein the mass ratio of ammonia water to ammonium persulfate in ammonia water-ammonium persulfate is 1:2, the manganese-zinc ferrite powder is mixed with polypropylene and KH570 in a mass ratio of 8:0.5:1.5 and ground for 2 hours to obtain a MnZn ferrite binder.

[0046] Example 1

[0047] This embodiment provides a method for preparing a high permeability and low loss amorphous magnetic powder core, comprising the following steps:

[0048] S1. Atomization powder making:

[0049] S11, smelting the raw materials to obtain an alloy solution:

[0050] The FeCoSiB alloy raw materials are prepared by smelting at 1550°C for 3h to obtain an alloy solution according to the mass percentage of Si: 6%, Co: 20%, B: 5%, Cr: 2%, Nd: 1%, Nb: 0.5%, Cu: 3%, Al: 4%, Ga: 2%, C: 0.5%, and the balance is Fe and impurities that are difficult to remove;

[0051] S12, in a mixed inert gas atmosphere, atomizing the alloy solution to obtain an alloy powder precursor:

[0052] Under the condition of vacuum degree of 5Pa, nitrogen, argon and a small amount of oxygen were filled in for mixed gas atomization treatment, the mass ratio of nitrogen, argon and oxygen in the mixed gas was 30:69.8:0.2, the alloy solution was atomized for 30min, the atomization pressure was 4.2Mpa, and the alloy powder precursor was obtained;

[0053] S13, cooling the alloy powder precursor to obtain amorphous alloy powder;

[0054] S2, particle size distribution:

[0055] The amorphous alloy powder obtained in step S1 is subjected to particle size classification to obtain a finished amorphous alloy powder having a fineness modulus D10 of 3 μm, a median particle size D50 of 11 μm, and a D90 of 18 μm;

[0056] S3, Inorganic-organic composite coating treatment:

[0057] S31, performing inner layer passivation treatment on the surface of the finished amorphous alloy powder obtained in step S2:

[0058] Take 100g of the finished amorphous alloy powder obtained in step S2 and heat it to 105°C, add 1.2g of sulfuric acid-phosphoric acid-boric acid composite passivation solution, wherein the mass ratio of sulfuric acid, phosphoric acid and boric acid is 20%:40%:40%, stir for 30min, and after stirring, dry at 110°C for 1h to obtain amorphous soft magnetic powder;

[0059] S32, performing outer insulation coating on amorphous soft magnetic powder:

[0060] Take 100g of amorphous soft magnetic powder, add 1g of polyacrylic acid-polyethylene glycol mixed solution, wherein the mass ratio of polyacrylic acid to polyethylene glycol is 40%:60%, stir for 30min, take out after stirring, and dry at 120°C for 1.5h to obtain amorphous soft magnetic powder after coating;

[0061] S33, taking 100g of the coated amorphous soft magnetic powder, adding 10g of the mixed solution of MnZn ferrite binder and acetone in Preparation Example 1, wherein the mass ratio of MnZn ferrite binder to acetone is 4:6, stirring for 30min, taking out after the stirring, drying at 120°C for 1.5h, and obtaining the finished amorphous magnetic powder;

[0062] S34, pressing the finished amorphous magnetic powder under a pressure of 1400 MPa for 15 seconds to form an amorphous magnetic powder core with an outer diameter of 14 mm and an inner diameter of 8 mm.

[0063] Example 2

[0064] Compared with Example 1, the present embodiment is different in that the step S12 "under the condition of a vacuum degree of 5 Pa, the mass ratio of nitrogen, argon and oxygen in the mixed gas is 30:69.8:0.2, the alloy solution is atomized for 30 minutes, the atomization pressure is 4.2 MPa, and an alloy powder precursor is obtained" is changed to "under the condition of a vacuum degree of 5 Pa, nitrogen, argon and a small amount of oxygen are filled into the mixed gas for atomization treatment, the mass ratio of nitrogen, argon and oxygen in the mixed gas is 40:59.8:0.2, the alloy solution is atomized for 30 minutes, the atomization pressure is 4.2 MPa, and an alloy powder precursor is obtained"; the remaining raw materials and preparation process remain the same as in Example 1.

[0065] Example 3

[0066] Compared with Example 1, the present embodiment is different in that the step S33 of "taking 100 g of the coated amorphous soft magnetic powder, adding 10 g of the mixed solution of MnZn ferrite binder and acetone in Preparation Example 1, wherein the mass ratio of MnZn ferrite binder to acetone is 4:6, stirring for 30 min, taking out after the stirring, drying at 120°C for 1.5 h, and obtaining the finished amorphous magnetic powder" is changed to "taking 100 g of the coated amorphous soft magnetic powder, adding 10 g of the mixed solution of MnZn ferrite binder and acetone in Preparation Example 1, wherein the mass ratio of MnZn ferrite binder to acetone is 2:8, stirring for 30 min, taking out after the stirring, drying at 120°C for 1.5 h, and obtaining the finished amorphous magnetic powder"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0067] Example 4

[0068] Compared with Example 1, the present embodiment is different in that the step S31 of "take 100g of the finished amorphous alloy powder obtained in step S2, heat it to 105°C, add 1.2g of sulfuric acid-phosphoric acid-boric acid composite passivation solution, wherein the mass ratio of sulfuric acid, phosphoric acid and boric acid is 20%:40%:40%, stir for 30min, and after stirring, place it at 110°C for 1h to dry to obtain amorphous soft magnetic powder" is changed to "take 100g of the finished amorphous alloy powder obtained in step S2, heat it to 105°C, add 1.2g of sulfuric acid-phosphoric acid-boric acid composite passivation solution, wherein the mass ratio of sulfuric acid, phosphoric acid and boric acid is 20%:50%:30%, stir for 30min, and after stirring, place it at 110°C for 1h to dry to obtain amorphous soft magnetic powder"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0069] Example 5

[0070] Compared with Example 1, the present embodiment is different in that the step S32 of "take 100g of amorphous soft magnetic powder, add 1g of polyacrylic acid-polyethylene glycol mixed solution, wherein the mass ratio of polyacrylic acid to polyethylene glycol is 40%:60%, stir for 30min, take out after stirring, dry at 120℃ for 1.5h, and obtain the amorphous soft magnetic powder after coating" is changed to "take 100g of amorphous soft magnetic powder, add 1.5g of polyacrylic acid-polyethylene glycol mixed solution, wherein the mass ratio of polyacrylic acid to polyethylene glycol is 50%:50%, stir for 30min, take out after stirring, dry at 120℃ for 1.5h, and obtain the amorphous soft magnetic powder after coating"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0071] Comparative Example 1

[0072] Compared with Example 1, the difference between this comparative example is that the "sulfuric acid-phosphoric acid-boric acid composite passivation solution" in step S31 is changed to "phosphoric acid"; step S32 is not performed after step S31 to perform outer insulation coating on the amorphous soft magnetic powder; the "10g of MnZn ferrite binder in Preparation Example 1" in step S33 is changed to "liquid methyl polysiloxane binder"; the remaining raw materials and preparation process remain the same as in Example 1.

[0073] Comparative Example 2

[0074] Compared with Example 1, the difference between this comparative example and Example 1 is that the "filling with nitrogen, argon and a small amount of oxygen for mixed gas atomization treatment, the mass ratio of nitrogen, argon and oxygen in the mixed gas is 30:69.8:0.2" in step S12 is changed to "filling with nitrogen"; the "10g of MnZn ferrite binder in Preparation Example 1" in step S33 is changed to "epoxy resin binder"; the remaining raw materials and preparation process remain the same as in Example 1.

[0075] Comparative Example 3

[0076] Compared with Example 1, the difference between this comparative example and this comparative example is that the "FeCoSiB series alloy raw materials are prepared in the mass percentage of Si: 6%, Co: 20%, B: 5%, Cr: 2%, Nd: 1%, Nb: 0.5%, Cu: 3%, Al: 4%, Ga: 2%, C: 0.5%, and the balance is Fe and impurities that are difficult to remove" in step S11 is changed to "FeCoSiB series alloy raw materials are prepared in the mass percentage of Si: 6%, Co: 20%, B: 8%, Cr: 5%, Cu: 3%, Al: 4%, C: 0.5%, and the balance is Fe and impurities that are difficult to remove"; that is, in the mass ratio of the raw materials, the three elements Ga, Nd and Nb are reduced compared with Example 1, and the specific gravity of Cr and B is increased; step S32 is not performed after step S31 to perform outer insulation coating on the amorphous soft magnetic powder; the remaining raw materials and preparation process remain the same as those in Example 1.

[0077] The magnetic permeability, loss, tap density, and DC bias of the amorphous magnetic powder cores prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were tested for performance, wherein the performance parameters of the magnetic permeability and DC bias were tested using a TH2840 series precision LCR digital bridge; the loss was tested using a MATS-22SA BH analyzer; and the tap density was tested using a tap density tester; the results are shown in Table 1:

[0078] Table 1

[0079]

[0080] It can be seen from Table 1 that the amorphous magnetic powder cores prepared in Examples 1 to 5 have higher magnetic permeability, lower loss, higher tap density, and better DC bias performance. Figure 1 This is a scanning electron microscope image of the double-layer insulation coating of the amorphous magnetic powder core prepared in Example 1. Figure 2 It is a schematic diagram of the effect of changes in magnetic induction intensity on the loss of different test cases.

[0081] Comparison between Comparative Example 1 and Example 1 shows that, first, internal passivation treatment is performed using a sulfuric acid-phosphoric acid-boric acid composite passivation solution, and then an external insulation coating is performed using a polyacrylic acid-polyethylene glycol mixed solution to achieve inorganic-organic composite coating treatment of the amorphous alloy powder, and a mixed solution of MnZn ferrite binder and acetone is used as a binder, which can significantly improve the magnetic permeability of the amorphous magnetic powder core and also significantly improve the loss.

[0082] Compared with Example 1, Comparative Example 2 uses a mixed gas atmosphere of nitrogen, argon and oxygen during atomization treatment. Compared with a single nitrogen atmosphere, the tap density of the amorphous magnetic powder core is effectively improved, thereby improving the magnetic permeability of the amorphous magnetic powder core; at the same time, the introduction of a small amount of oxygen will form a tight oxide layer on the surface of the amorphous alloy powder, thereby reducing the loss of the amorphous magnetic powder core.

[0083] Comparison between Comparative Example 3 and Example 1 shows that the DC bias performance of the amorphous magnetic powder core is significantly improved by adding rare alloy elements such as Ga, Nd, and Nb. First, internal passivation treatment is performed using a sulfuric acid-phosphoric acid-boric acid composite passivation solution, and then external insulation coating is performed using a polyacrylic acid-polyethylene glycol mixed solution to achieve an inorganic-organic composite double-layer coating of the amorphous alloy powder. Compared with the use of a sulfuric acid-phosphoric acid-boric acid composite passivation solution for internal passivation treatment to achieve a single-layer coating, the improvement in magnetic permeability is more obvious than the single-layer coating treatment. This is because the double-layer coating can effectively isolate the eddy current path of the magnetic amorphous alloy powder, thereby significantly reducing the loss of the amorphous magnetic powder core.

[0084] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high permeability and low loss amorphous magnetic powder core, characterized in that: The steps include: S1, atomization powder making; S2, particle size gradation; S3, inorganic-organic composite coating treatment; In the atomization powder making process, a mixed inert gas is used for atomization treatment, and the mixed inert gas is nitrogen, argon and a small amount of oxygen; in the inorganic-organic composite coating process, a sulfuric acid-phosphoric acid-boric acid composite passivation solution is first used for internal passivation treatment, and then a polyacrylic acid-polyethylene glycol mixed solution is used for external insulation coating, and a MnZn ferrite binder and acetone mixed solution is used for bonding.

2. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 1, characterized in that: Step S1: atomization powder making comprises the following steps: S11, smelting the raw materials to obtain an alloy solution; S12, atomizing the alloy solution under a mixed inert gas atmosphere to obtain an alloy powder precursor; S13, cooling the alloy powder precursor to obtain amorphous alloy powder.

3. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 2, characterized in that: The raw material in step S11 is a FeCoSiB alloy. Preferably, the components of the raw material include, by mass percentage: Si: 2-8%, Co: 15-25%, B: 3-8%, Cr: 0.5-3%, Nd: 0.5-2%, Nb: 0.5-5%, Cu: 0.5-5%, Al: 0.5-5%, Ga: 0.5-5%, C: 0.1-2%, and the remainder is Fe and impurities that are difficult to remove; The smelting temperature in step S11 is 1350° C.-1500° C., and the smelting time is 2-3 hours.

4. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 2, characterized in that: The mass ratio of nitrogen, argon and oxygen in the mixed inert gas in step S12 is 30%-40%: 60%-70%: 0.2%; The atomization pressure of the atomization process in step S12 is 2.5-5 MPa, and the atomization time is 20-40 min.

5. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of step S2 particle size distribution are: The amorphous alloy powder obtained in step S1 is subjected to particle size classification to obtain a finished amorphous alloy powder having a fineness modulus D10 of 3-5 μm, a median particle size D50 of 10-12 μm, and a D90 of 16-19 μm.

6. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 1, characterized in that: Step S3: Inorganic-organic composite coating treatment includes the following steps: S31, performing inner layer passivation treatment on the surface of the finished amorphous alloy powder obtained in step S2: heating the finished amorphous alloy powder obtained in step S2 to 103-110° C., adding sulfuric acid-phosphoric acid-boric acid composite passivation solution and stirring for 20-30 min, and drying at 105-120° C. for 0.5-1.5 h after the stirring, to obtain amorphous soft magnetic powder; S32, performing outer insulation coating on the amorphous soft magnetic powder: adding polyacrylic acid-polyethylene glycol mixed solution to the amorphous soft magnetic powder and stirring for 20-30 minutes, taking out after the stirring, and drying at 110-130° C. for 1-2 hours to obtain the coated amorphous soft magnetic powder; S33, mixing the MnZn ferrite binder and acetone mixed solution into the coated amorphous soft magnetic powder, stirring for 20-30 minutes, taking out after the stirring, and drying at 120-140° C. for 1-2 hours to obtain a finished amorphous magnetic powder; S34, pressing the finished amorphous magnetic powder under a pressure of 1200-1600 MPa for 10-20 seconds to form an amorphous magnetic powder core with an outer diameter of 14 mm and an inner diameter of 8 mm.

7. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 6, characterized in that: In step S31, the mass ratio of sulfuric acid-phosphoric acid-boric acid composite passivation solution to finished amorphous alloy powder is 2‰-14‰, and the mass ratio of sulfuric acid, phosphoric acid and boric acid in the sulfuric acid-phosphoric acid-boric acid composite passivation solution is 20%-30%: 40%-50%: 30%-40%.

8. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 6, characterized in that: In step S32, the mass ratio of the polyacrylic acid-polyethylene glycol mixed solution to the amorphous soft magnetic powder is 5‰-15‰, and the mass ratio of polyacrylic acid to polyethylene glycol in the polyacrylic acid-polyethylene glycol mixed solution is 40%-50%:50%-60%.

9. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 6, characterized in that: In step S33, the mass ratio of the MnZn ferrite adhesive to the amorphous soft magnetic powder after the coating process is 2-4%, and the mass ratio of the acetone solution to the amorphous soft magnetic powder after the coating process is 4-8%.

10. The method for preparing a high permeability and low loss amorphous magnetic powder core according to claim 6, characterized in that: The MnZn ferrite binder in step S33 is prepared by the following steps: The iron salt, manganese salt and zinc salt are prepared into an iron-manganese-zinc solution in a mass ratio of 6:2:2, n-hexanol and sodium dodecylbenzene sulfonate are prepared into n-hexanol-sodium dodecylbenzene sulfonate in a mass ratio of 1:3, the iron-manganese-zinc solution and the n-hexanol-sodium dodecylbenzene sulfonate with a mass ratio of 5‰ of the iron-manganese-zinc solution are mixed, and then 1% ammonia water-ammonium persulfate with a mass ratio of ammonia water to ammonium persulfate of the iron-manganese-zinc solution is added to prepare manganese-zinc ferrite powder, wherein the mass ratio of ammonia water to ammonium persulfate in ammonia water-ammonium persulfate is 1:2, the manganese-zinc ferrite powder is mixed with polypropylene and KH570 in a mass ratio of 8:0.5:1.5 and ground for 2 hours to obtain a MnZn ferrite binder.

Citation Information

Patent Citations

  • FeSiBPNbCr amorphous magnetic powder and preparation method thereof

    CN114309628A

  • Preparation method of iron-based amorphous magnetic powder core

    CN116435085A

  • High saturation magnetic induction intensity iron-based amorphous soft magnetic composite material and manufacturing method thereof

    CN104036904A

  • Magnetic core and method for producing the same

    CN106486236A

  • Novel spherical iron-based amorphous alloy powder and preparation method of amorphous magnetic powder cores

    CN108010654A